Analysis of Phonological Errors of Morphology and Synthxis in Description Text in VII Class Students of Middle School 60 Palembang - Oktareza, Dede; Wardarita, Ratu; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to describe the errors of phonology, morphology and syntax in descriptive text for seventh grade students of Middle School 60 Palembang. The method used in this research is a descriptive qualitative method. The data source of this research is the descriptive text of the students, amounting to 150 students. The data from this study were words or sentences that experienced morphological and syntactic phonological errors. The data collection techniques from this research were test and interview techniques. The data analysis method used in this research is the triangulation collection method. The results of this study found that the most dominant errors were errors in the phonological field. The phonological errors found were misuse of punctuation marks, errors in using prepositions, errors in using capital letters and errors in writing basic words. Morphological errors include affixation errors. Syntax errors include inefficient sentences.